A temporal analysis of the u48kg women`s judo in the 2010 World Championships - Challis, D. (2011)
Developing an understanding of the work to rest ratios and the contribution of different technical components within a contest can assist coaches in developing training methodology that is time effective.This study aimed to develop an understanding of the under 48kg division. Pre-recorded footage was coded into temporal sequences. The results showed that on average there were 12.3 temporal blocks (hajime-matte) per contest, this was divided into kumi kata (32%), attack/defend (26%), transition/ newaza (19%) and matte (23%) of the contest. Furthermore the average duration of the contest, including matte blocks was 5.53minutes. Some of the results of this study concur with previous research.